Выдающиеся крымскотатарские деятели музыкального искусства - Алиева, З. (Культура народов Причерноморья, 2013)
Outstanding Crimean Tatar musical figures have played a significant role in shaping the modern musical art of the Crimean Tatars. Asan Refat – the first Crimean Tatar professional composer, social activist and educator. He laid the foundation for harmonization and orchestration of the Crimean Tatar folk songs and melodies. Refat took an active part in the ethnographic expeditions in collecting and recording folk music of the Crimean Tatars. He worked closely with the scientific world . Wrote the first theoretical writings on music of the Crimean Tatars. Asan Refat was the founder of the first Crimean Tatar Opera – "Chora Batyr". Publication music collection "Sounds haytarma". Sherfedinov skillfully mastered the violin. At the end of the Moscow Conservatory worked as music director of Simferopol Radio Committee. Written a number of musicals and comedies. Composed a choral suite and a cantata for chorus. Sabriye Eredzhepova – the legendary Crimean Tatar singer. She has participated in vocal competitions in Moscow. Her repertoire consisted not only of the Crimean Tatar folk songs, but also songs of the peoples of the USSR and the works of the classical repertoire. Sabriye Eredzhepova was the first soloist of the Crimean Tatar Song and Dance Ensemble "Haytarma". Her book is an invaluable memories of the outstanding figures of the Crimean Tatar music. Ilyas Temirovich Bakhshish – a talented composer, conductor, teacher and public figure . His musical career he began in the Crimean radio committee . Bakhshish was prepared for publication by a number of musical works, including choral and vocal works. He actively promoted the Crimean Tatar folk music on stages, radio and recorded it on the plates . Bakhshish was the head of the Crimean Tatar ensemble "Haytarma". Arranged the Crimean Tatar folk songs and melodies. Bakhshish published compilations of the Crimean Tatar songs. A great contribution to the conservation of the cultural heritage of the Crimean Tatar makes Fevzi Aliyev – composer, folklorist and singer. For several years he was the musical director and conductor of the State Song and Dance Ensemble "Haytarma". He actively promoted among the young Crimean Tatar folk songs and melodies. The great achievement of Fevzi Aliyev is the creation of "Anthology of the Crimean folk music". Noteworthy social and educational activities F. Aliyev.